Ruzigrass Grown in Rotation with Soybean Increases Soil Labile Phosphorus - Almeida, Danilo S.; Rosolem, Ciro A. (Agronomy journal, 2016)
Crop rotations with species able to solubilize soil P can result in improved P availability for subsequent crops. Ruzigrass [Urochloa ruziziensis (R. Germ. and C.M. Evrard)] has been shown to increase soil available P, but there are few studies on its effect on soil P forms and how growing ruzigrass interacts with P fertilization, which is important in defining fertilization strategies. This study aimed to investigate soil P fractions resulting from cropping ruzigrass in rotation with soybean [Glycine max (L.) Merr.] fertilized with broadcast triple superphosphate (TSP) or reactive rock phosphate (RRP) and TSP applied to soybean furrows under no‐till. Soil samples were taken after ruzigrass desiccation and before soybean planting from long‐term experimental plots in Botucatu, in southeastern Brazil. Phosphate management included RRP and TSP broadcast on the soil surface, and TSP applied to soybean furrows, in the presence or absence of ruzigrass. Broadcast TSP increased labile (anion exchange resin‐extractable P) and moderately labile P fractions extracted with 0.1 M NaOH, whereas RRP increased moderately labile P extracted with HCl. There was no interaction between phosphate management configurations. Regardless of phosphate management, the presence of ruzigrass resulted in a lower residual‐P concentration in deeper soil layers and higher concentrations of labile and moderately labile P in the uppermost soil layers. Ruzigrass introduction into the cropping system resulted in higher soil labile P content compared with fallow, probably because it can take up moderately labile soil P fractions that are recycled into the system, regardless of the P fertilization strategy. Core Ideas Ruzigrass grown in soybean off‐season affects soil fertility. Soil P cycling by ruzigrass may result in benefits to next crops. Agronomic efficiency of phosphate fertilizers may be improved by ruzigrass.